Isomer-Free Quinoidal Building Block Employing 3,4-Phenylenedioxythiophene Unit with Mesomeric Effect for Low- Bandgap Quinoidal Conjugated Polymers - Choi, Yeonsu; Kim, Yunseul; Moon, Yina; Hwang, Kyoungtae; Hong, Jeongjin; Kim, Younghyo; Kim, Dong-Yu (American Chemical Society, 2023)
Quinoidal compounds have attractive features as organic semiconducting materials owing to their distinct properties compared to aromatic compounds. The suppression of geometrical isomers is a challenge in the development of quinoid-type molecules. In this study, a novel quinoidal building block, bQuPheDOT-Br, was synthesized by incorporating 3,4phenylenedioxythiophene (PheDOT). Using the conformation-locking strategy, bQuPheDOT-Br exists as a single isomeric compound with a planar molecular structure, resulting in effective pi-electron delocalization. Two quinoidal conjugated polymers, PbQPheDOT-T2 and PbQPheDOT-2FT2, were synthesized. Owing to the planar geometry and possible electron delocalization due to the phenyl ring incorporation of the bQPheDOT unit, PbQPheDOT-T2 and PbQPheDOT-2FT2 exhibited a low bandgap (similar to 1.3 eV) and near-infrared (NIR) light absorption up to 1200 nm wavelength due to the mesomeric effect. Grazing-incidence wide-angle X-ray scattering revealed that both polymers exhibited high crystallinity up to the fourth order of the (h00) diffraction peaks after thermal annealing, owing to their rigid and planar quinoidal backbone. Finally, the charge transport properties of PbQPheDOT-T2 and PbQPheDOT-2FT2 were evaluated by fabricating organic field-effect transistors as active layers with hole mobilities of 5.2 x 10-2 and 2.6 x 10-2 cm2/Vs, respectively, and electron mobility of 1.0 x 10-2 cm2/Vs for PbQPheDOT-T2.